The Model of The Archipelago's Maritime Muslim City in Medieval Times (A Study of Somba Opu in the Kingdom of Makassar) - Syukur, Syamzan; Suraya Rasyid; Rahmat; Rahmawati; Mastanning (Al-Hikmah Journal for Religious Studies, 2024)
The purpose of this study is to reconstruct Somba Opu as a model of the Muslim maritime city of the archipelago in medieval times. The results of this study will be useful for the government of South Sulawesi Province, especially in determining policies related to urban planning and urban governance (good urban governance). The types of research used are library research and field research. Library research focuses on reviewing, studying, and discussing literature or library sources and other sources. Filed research captures actual data and information at the research location. The research steps are Heuristics, Criticism, Interpretation, and historiography. The results of this study show that Somba Opu grew to become one of the maritime Muslim Cities in the archipelago in the 17th century. The characteristics include; Somba Opu is the center of the Makassar Kingdom government as well as an international commercial city visited by foreign traders from Asia (China, Malay, India, and Arabia) and from Europe such as Portugal, so the population grew significantly and pluralist, coastal markets grew into economic centers and private and foreign companies providing employment, the existence of the Mosque as a symbol of Islamic government with a majority Muslim population. The king with the title of Sultan was Sultan Alauddin and the kings after him. This Islamic government respects the plurality of society which is marked by the existence of non-Muslim houses of worship such as churches that are permitted by the ruler. The results of this study will complement and enrich previous studies as well as become a reference for urban managers and urban planning experts.